Rare and unusual snow leopard encounters in the broadleaf forest of the Bhutanese Himalayas - Dorji, Rinzin; Letro; Yangden, Sonam; Dendup, Pema; Dhendup, Tashi; Lhamo, Yangchen (Snow Leopard Reports, 2024)
The snow leopard Panthera uncia, a top predator in Central and South Asia, faces population declines due to habitat degradation, prey depletion, retaliatory killings, poaching, and climate change. In Bhutan, where the species is protected, we report two rare sightings in the Gedu regionʼs broadleaved and fir forests, at 2,708 masl and 3,839 masl, respectively, which are lower than the typical speciesʼ prime habitats in Bhutan. These findings suggest that this area may function as an important corridor or a potential range expansion beyond typical high-altitude habitats (3,000 to 5,800 masl). This discovery underscores the speciesʼ ecological adaptability and highlights the need for enhanced conservation strategies, including habitat connectivity mapping and local community education. Additionally, it highlights the importance of protecting and conserving habitats outside of protected areas for speciesʼ long-term persistence.